Gaia sky: navigating the Gaia catalog - Sagristà Sellés, Antoni; Jordan, Stefan; Sadlo, Filip; Müller, Thomas (IEEE transactions on visualization and computer graphics, 2019)
In this paper, we present Gaia Sky, a free and open-source multiplatform 3D Universe system, developed since 2014 in the Data Processing and Analysis Consortium framework of ESA's Gaia mission. Gaia's data release 2 represents the largest catalog of the stars of our Galaxy, comprising 1.3 billion star positions, with parallaxes, proper motions, magnitudes, and colors. In this mission, Gaia Sky is the central tool for off-the-shelf visualization of these data, and for aiding production of outreach material. With its capabilities to effectively handle these data, to enable seamless navigation along the high dynamic range of distances, and at the same time to provide advanced visualization techniques including relativistic aberration and gravitational wave effects, currently no actively maintained cross-platform, modern, and open alternative exists.
Date of publication 16 Aug. 2018; date of current version 21 Oct. 2018
Gesehen am 30.08.2019